2022
DOI: 10.21608/ejhc.2022.252382
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ performance regarding Infection Control Precautions in Primary Health Care Centers

Abstract: Background: Standards precautions are designed to protect staff from risks resulting from exposure to blood and body fluids and to protect patients from potential cross infection. Knowledge of clinical infection control practices is continually growing and changing. Therefore, the aim of the study was to assess nurses' performance regarding infection control precautions in primary health care centers. Research design: a descriptive analytical design had been used. Subjects: simple random sample of a total of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…Regarding correlation between nurses' knowledge and practices scores, a statistically significant positive correlation between nurses' knowledge and practice was noticed; which reflects that nurses' performance is mainly based on their knowledge. In agreement with the current study finding Mhana et al, (2022) (28) and Elrefaey, et al (2021) (29) noticed that; nurses' practices are precisely affected by their base of knowledge which is crucial to reach competent nursing practices in diverse clinical settings. Moreover, Enterprise in association with CIRA (2023) (30) declared that, not merely knowledge is the foundation stone in nursing practice; but also deficient of educating combined with their shortage, being the accountable staff supplying a major part of healthcare.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding correlation between nurses' knowledge and practices scores, a statistically significant positive correlation between nurses' knowledge and practice was noticed; which reflects that nurses' performance is mainly based on their knowledge. In agreement with the current study finding Mhana et al, (2022) (28) and Elrefaey, et al (2021) (29) noticed that; nurses' practices are precisely affected by their base of knowledge which is crucial to reach competent nursing practices in diverse clinical settings. Moreover, Enterprise in association with CIRA (2023) (30) declared that, not merely knowledge is the foundation stone in nursing practice; but also deficient of educating combined with their shortage, being the accountable staff supplying a major part of healthcare.…”
Section: Discussionsupporting
confidence: 91%
“…On the same line, Anwar et al, (2019) (27) study conducted among nursing staff in an Egyptian and a Saudi hospital found that; the majority of nurses' practices were unsatisfactory when they administer medications via IV access devices. On the contrary, Mhana et al, (2022) (28) in Egypt reported that, about two thirds of nurses had satisfactory practices when refrained to safe IV administration.…”
Section: Discussionmentioning
confidence: 96%
“…Knowledge is closely related to nurse performance ( Ryusuke & Sanica, 2021 ; Sarumi & Sari, 2022 ; Tesfaye & Abera, 2015 ). In addition, less knowledge can impact poor infection control ( Ibrahim Abdeen Mhana et al, 2022 ). Previous studies showed there was a significant positive correlation between nurse knowledge and nurse performance ( Hidayah & Putri, 2020 ; Jumoke & Mutula, 2018 ).…”
Section: Discussionmentioning
confidence: 99%